2021
DOI: 10.20944/preprints202107.0456.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Benefits of a Switch From Intermittently Scanned Continuous Glucose Monitoring (isCGM) to Real-time (rt) CGM in Diabetes Type 1 Suboptimal Controlled Patients in Real-life: A One-year Prospective Study

Abstract: The switch from intermittently scanned continuous glucose monitoring (isCGM) to real-time (rt) CGM could improve glycemic management in suboptimal controlled type 1 diabetes patients, but long-term study is lacking. We evaluated retrospectively the ambulatory glucose profile (AGP) in such patients after switching from Free Style libre 1 (FSL1) to Dexcom G4 (DG4) over 1 year. Patients (n=21, 43±15 years, BMI 25±5, HbA1c 8.1±1.0%) had severe hypoglycemia and/or HbA1c≥8%. A… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Large glucose variability might increase oxidative stress and inflammation, which cause endothelial cell damage 25 and increase cardiovascular risk 26 . Several studies have shown that rtCGM is superior to isCGM in terms of reducing the TBR, and improving the TIR and HbA1c levels in adult patients with type 1 diabetes [7][8][9][10][11] . Reddy et al 7 and Pr eau et al 10 reported that switching from isCGM to rtCGM reduced TBR and increased TIR in patients with type 1 diabetes, and suggested switching from isCGM to rtCGM as an alternative to changing the insulin delivery system in patients with suboptimal glycemic control.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Large glucose variability might increase oxidative stress and inflammation, which cause endothelial cell damage 25 and increase cardiovascular risk 26 . Several studies have shown that rtCGM is superior to isCGM in terms of reducing the TBR, and improving the TIR and HbA1c levels in adult patients with type 1 diabetes [7][8][9][10][11] . Reddy et al 7 and Pr eau et al 10 reported that switching from isCGM to rtCGM reduced TBR and increased TIR in patients with type 1 diabetes, and suggested switching from isCGM to rtCGM as an alternative to changing the insulin delivery system in patients with suboptimal glycemic control.…”
Section: Discussionmentioning
confidence: 99%
“…Third, several reports have shown the hypoand hyperglycemia alert systems and an alert system against excessive hypoglycemia available with rtCGM have beneficial effects [7][8][9][10][11]27 . In particular, the low-glucose alert with rtCGM can greatly contribute to reducing TBR because patients can respond in a timely manner to hypoglycemia during exercise and in daily self-management 9,10 , and during the night when they would otherwise be unaware of hypoglycemia 7,8 . Visser et al 11 showed that patients on rtCGM were less concerned about developing hypoglycemia, because the low-glucose alert and urgent low-glucose alarm reduced their risk of developing hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have demonstrated that both isCGM and rtCGM are superior to self-monitoring of blood glucose (SMBG) for achieving optimal glycemic control and improving the quality of life in patients treated with MDI or an insulin pump [9,[17][18][19], whereas some studies have indicated that rtCGM is better than isCGM in terms of reduction of hypoglycemia and improvement of glycemic control in adults with type 1 diabetes [20][21][22][23][24]. Reddy et al [20] and Préau et al [23] reported that switching from isCGM to rtCGM decreased TBR and simultaneously increased TIR in patients with type 1 diabetes. They suggested switching from isCGM to rtCGM as an alternative to changing the insulin delivery system in patients with suboptimal glycemic control.…”
Section: Cgm Metrics In Intermittently Scanned Cgm (Iscgm) and Real-t...mentioning
confidence: 99%